Social and Economic Standing of Low-Income Groups of Population in Conditions of Inflation Rate Growth and Volatility of Customer Prices - D. V. Nekipelova (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article analyzes social and economic standing of low-income people. In spite of legislative standards protecting key groups of socially vulnerable population from absolute poverty such categories, as old-age pensioners, disabled persons, young children and even employable population, the so-called poor workers still belong to the low-income population. It is obvious that the major proportion of low-income people consists of individuals, who get allowances and social payments therefore their financial provision depends mainly on state. When poverty proliferates among the population of the Russian Federation, the development of the effective model of material provision for people dependable on state, for instance indexation of various social payments with due regard to the inflation rate and volatility of consumer prices is an essential challenge of today. It is especially acute in the current situation, when home economy encounters constant pressure, the more effective the model will become, the quicker the goals aimed at cutting the poverty rate and improving social and economic standing of people will be attained. However, the model shall be developed and other steps taken with due regard to realistic possibilities of federal and regional budgets.